Exosomal miRNA Analysis of Aqueous Humour of Diabetes and Cataract Patients. (4th March 2021) - Gao, Chao; Fan, Fan; Liu, Xin; Yang, Jianing; Zhou, Xiyue; Mei, Hengjun; Lin, Xiaolei; Luo, Yi
ABSTRACT: Background: The mechanism of diabetes and cataracts is complicated. Considering our increasing acknowledge of exosomes, exosomal miRNAs isolated from aqueous humour (AH) may play an important role in the mechanism of diabetes and cataracts. Our study aimed to isolate exosomes from human aqueous humour and study the functions of exosomal miRNAs on human lens epithelial cells (HLECs). Results: MiRNA sequencing revealed that 295 miRNAs were upregulated and 138 miRNAs were downregulated in exosomes of the diabetes and cataracts group (DMC) compared with the age-related cataracts group (ARC), among which miR-551b was highly expressed with a log2 fold change of 5.99. GO and KEGG analyses indicated that the predicted genes were mainly involved in cadherin binding, proteoglycans in cancer and AGE-RAGE signalling pathway in diabetic complications. We then examined the function of miR-551b and found that miR-551b reduced the viability and increased the apoptosis of HLECs by downregulating CRYAA expression. Conclusions: Exosomes isolated from human aqueous humour contained abundant miRNAs. A highly expressed miRNA, miR-551b, could regulate the functions of HLEC by targeting CRYAA. Methods: We pooled all the aqueous humour of each group into one sample and isolated exosomes from human aqueous humour by ultracentrifugation, measured the size and concentration of exosomes by nanoparticle tracking analysis (NTA), observed the morphology of exosomes by transmission electron microscopy (TEM), and sequenced exosomal miRNAs. We performed bioinformatic analysis of the sequencing results, including GO analysis and KEGG pathway enrichment. We then examined CRYAA mRNA expression levels and protein levels by quantitative real-time PCR and Western blot. Cell Counting Kit-8 and flow cytometry were applied to examine cell viability, proliferation and apoptosis.